Exploring the impact of virtual leadership on job satisfaction in the post-COVID-19 era: The mediating role of work–life balance and trust in leaders - Al Dilby, Hala Koleilat; Farmanesh, Panteha (Frontiers in Psychology, 2023)
With increased number of business turning to virtual workspaces to conduct their businesses in the aftermath of COVID-19 pandemic, the role of leaders in managing psychological behavior and wellbeing of employees has become more pivotal. Accordingly, this research follows a recent string of studies that examine the role of virtual leaders in increasing job satisfaction of employees. We further argue that trust in leader and work-life balance have a mediating effect on the virtual leader-job satisfaction relationship. In this sense, this study uses data from IT employees as a high-performance sector. With a total of 196 respondents and using PLS-SEM, virtual leaders were found to be influential on job satisfaction of IT staff, while trust in leader and work-life balance have been found to have mediation effect. The findings of this research show statistical significance that suggest a number of positive work outcomes and pathways with scholarly and managerial implications that can be beneficial for leaders in relevant sectors.